Back pain in patients with comorbid central nervous system pathology: how to select the right non-steroidal anti-inflammatory preparation - V. V. Razdorskaya; O. V. Kolokolov; G. K. Yudina (Лечащий Врач, 2021)
Approaches to selection of non-steroidal anti-inflammatory preparations in back pains in patients with comorbid central nervous system pathology were considered, in order to ensure fast, reliable and safe pain relief in the way convenient for the patient.